The Impact of Cognitive Reserve and Emotional Affect on Working Memory Performance Among Younger and Older Adults: A Multiple Moderation and Neuroimaging Investigation - Franklin, Dylan (Université d'Ottawa / University of Ottawa, 2024)
Canada's population is aging rapidly, with the number of older adults 65+ expected to reach over one billion within the next ten years. Aging is often associated with cognitive decline and is something that many older adults fear. Thus, it is imperative to conduct aging-related research to determine if there is anything that can be done to postpone cognitive decline and improve the ability to age successfully. Within recent years, the discussion surrounding mental health and emotional wellbeing has been at the forefront of many news articles and research studies. Our emotions play a vital part in all aspects of our lives, including our cognitive abilities. Experiencing more positive emotions has been associated with greater brain activation which helps build up cognitive and psychological resources that may be useful later in life. In addition to our emotions, another protective factor such as cognitive reserve has been extensively studied within recent decades. Cognitive reserve cannot be studied directly as of yet, so various proxies of cognitive reserve such as education or occupation have been included in previous research studies. Cognitive reserve has been theorized as something that an individual can build up throughout their lifetime and could help preserve cognitive abilities later in life when age-related brain changes occur, or the effects of neurodegeneration are more prevalent. Although previous research has noted the significant impact emotions and cognitive reserve have on memory, few studies have assessed how both could potentially moderate the association between age and working memory performance. Thus, the current study used multiple moderation to investigate this association using a sample of healthy young (n=50) and older (n=46) adults and a delayed match-to-sample letter task. Cognitive reserve was assessed using years of education as a proxy, and emotional affect was assessed using the positive and negative affect schedule questionnaire. Every participant was asked to complete this questionnaire at the start of each testing session to indicate how they were feeling at that moment. An average score for positive and negative affect was calculated, with higher scores reflecting greater positive/negative affect, and lower scores reflecting lower positive/negative affect. Based on results from the first session, significant multiple moderation was found. The interaction between age and cognitive reserve was significant, as well as the interaction between age and positive affect. Specifically, these results indicated a strong age effect which demonstrated that younger adults with greater cognitive reserve and positive affect performed better on the working memory task compared to older adults (b=1.04, p<0.001). This effect was also noticeable when cognitive reserve was low and positive affect was high (b=0.41, p=0.001), suggesting that emotional wellbeing can aid in working memory performance even when cognitive reserve is lower. Additional analyses combined the response time and accuracy values together using the inverse efficiency score to better assess the differences or similarities between this combined score and response times alone. Results from these models also found significant multiple moderation, and the effects were even stronger. The impact of negative affect was assessed in separate multiple moderation models, but no significant effect of moderation was found regarding negative affect; however, cognitive reserve continued to remain a significant moderator in all models. Results from the second session utilized data that was taken while participants completed the same working memory task in an MRI to assess brain-related changes between both age groups. A reduced sample of younger adults (n=41) and older adults (n=40) was used since some participants were not able to complete this portion of the study. No significant multiple moderation was found during the second session; however, the main effect of age remained significant across all models. Using SPM12, various brain regions were identified in which older adults recruited more brain activity in order to complete the working memory task. These regions included the left precentral gyrus, right lingual gyrus, and right postcentral gyrus, which are comparable to other studies that used a similar task. Overall, the results from this study build off the previous literature surrounding emotions and cognitive reserve and highlights the importance of emotional wellbeing and cognitive reserve as we age. By clarifying the role these variables play, various changes could be made throughout an individual's life to strengthen one's emotional wellbeing and cognitive reserve, which may help later on in life when age-related brain changes or neurodegeneration may occur.
Keywords: Emotional Affect; Cognitive Reserve; Multiple Moderation; Neuroimaging